PERAN AKUNTAN DALAM MENANGANI KASUS HUKUM YANG MELIBATKAN PENYALAHGUNAAN DANA PUBLIK DI KOTA SERANG - Islami, Norma; Qurba, Harry; Faturohman, Faturohman; Jumhana, Enjum (Bhinneka Multidisiplin Journal, 2024)
This study investigates the role of forensic accountants in addressing public fund misappropriation in Serang City, focusing on their involvement in legal proceedings. Using a qualitative case study method, the research examines financial audit reports, interview data with forensic accountants, and legal documents to understand how these professionals detect and prevent fraud. Forensic accountants analyze financial records to identify discrepancies and suspicious activities, utilizing advanced data analysis tools to uncover hidden misappropriations. The research highlights the importance of collaboration between forensic accountants and legal institutions to expedite case resolution and ensure accountability. It also emphasizes the need for specialized training and a deep understanding of local contexts to effectively address fraud. This study demonstrates the critical role of forensic accounting in promoting transparency, accountability, and integrity in public financial management.